A Novel CuBi2O4/BiOBr Direct Z‐scheme Photocatalyst For Efficient Antibiotics Removal: Synergy of Adsorption and Photocatalysis on Degradation Kinetics and Mechanism Insight. Issue 17 (17th July 2020) - Huang, Shushu; Wang, Guodong; Liu, Jiaqi; Du, Chunfang; Su, Yiguo
Abstract: A novel direct Z‐scheme CuBi2 O4 /BiOBr heterostructural photocatalyst was developed aiming to modulate the adsorption ability and photocatalytic degradation performance toward antibiotics. Tetracycline as the model antibiotics was found to show pH value and temperature dependent adsorption capacity over CuBi2 O4 /BiOBr. The adsorption process was fitted to Pseudo‐second‐order and Elovich kinetic models and adsorption isotherm was followed Freundich isotherm model. Junction of CuBi2 O4 and BiOBr can modulate the surface feature and interfacial interactions, leading to direct Z‐scheme charge kinetics for improved photocatalytic activity. The adsorptive capability and photocatalytic performance of CuBi2 O4 /BiOBr heterojunction showed great improvement in comparison with pristine CuBi2 O4 and BiOBr. The mineralization process and intermediates for tetracycline degradation were identified by total organic carbon analysis and liquid chromatograph‐tandem mass spectrometry. Plausible transformation pathway and photocatalytic mechanism were proposed. Radical trapping experiments indicated that photogenerated holes and ⋅O2 − active species played crucial roles in photocatalytic tetracycline decomposition. Abstract : Anti‐antibiotics : Construction of direct Z‐scheme CuBi2 O4 /BiOBr heterojunction photocatalyst achieved exceptional adsorption and photocatalytic degradation performance toward antibiotics.